New post‐ACA insurance data highlights health insurer spending on health care quality. Issue 2 (22nd May 2020) - Tice Sirmans, E.; Steinorth, Petra
Abstract: Following the Patient Protection and Affordable Care Act (ACA), annual financial reports by commercial health insurers include more detailed information on a Supplemental Health Care Exhibit. In this new exhibit, insurers illustrate spending on the provision of medical services and associated expenses. These expenses, which were commonly reported as "claims adjustment" and "general administrative" expenses, can now be allocated to several new categories of expenses associated with combatting fraud and improving patient health care quality. This article illustrates that quality improvement expenses have increased significantly in the individual, small group, and large group markets following implementation of the ACA. Of the five types of quality expenses reported, the greatest proportion of spending has been toward the improvement of health outcomes and the most pronounced increase from 2011 to 2017 has been spending toward increased wellness and health promotion activities, which include activities such as wellness assessments and coaching programs for patients with chronic diseases. Given that the ACA was designed not only to broaden access to health insurance but also to improve health, analysis of the allocations to various types of quality improvement activities highlights the private market's contribution to improving the health of the US population.